Low cycle fatigue behavior of modified 9Cr-1Mo steel at room temperature - Verma P.; Srinivas N.C.S.; Singh S.R.; Singh V. (My University, 2025)
Low cycle fatigue (LCF) behavior of modified 9Cr-1Mo steel was studied in normalized and tempered condition at strain rates from 10-2s-1 to 10-4s-1 in the regime of low strain amplitude between ±0.25% and ±0.5% at room temperature. Cyclic softening was exhibited at the higher strain amplitudes of ±0.375% and ±0.50% after about 20-30 cycles and after 200-300 cycles at the lowest strain amplitude of ±0.25%, at all the strain rates. There was mild tendency of hardening from 2 to 20 cycles at the highest strain amplitude of ±0.50% and up to 200-300 cycles at the lowest strain amplitude of ±0.25%. The rate of softening increased with increase in strain amplitude. Masing and non-Masing behavior was exhibited at the higher strain amplitudes (≥±0.375%) and lower strain amplitudes (<±0.375%) respectively. Dependence of fatigue life, based on both plastic strain amplitude as well as plastic strain energy was linear and fatigue life decreased with lowering of strain rate. The unstable tempered martensitic structure was transformed into equiaxed dislocation cell structure under cyclic loading. The size of the cells and annihilation of dislocations increased with increase in strain amplitude. While the friction stress decreased with number of cycles at all the strain amplitudes, back stress was nearly constant at the high strain amplitudes and increased at the lowest strain amplitude. The observed cyclic softening was thus mainly due to decrease in friction stress, formation of low energy dislocation cell structure, and annihilation of dislocations. © 2015 Elsevier B.V..